Letter from Mickey Wapner - Mickey Wapner:::::: (1966)
A letter from the Women's Campaign to Re-Elect Governor Brown invites Democratic women to become actively involved in the general election campaign. The writer notes a surge of interest from women volunteers following the primary election and urges them to join before the July 4th holiday. Recipients are invited to attend a working campaign meeting on June 28 at the Southern California headquarters in Los Angeles. The letter emphasizes Governor Brown's desire to begin campaigning immediately rather than waiting until Labor Day. It frames the campaign as an opportunity to counter "ultra-conservatism" and encourages women to enroll and participate.